The Voting Rights Issue of Officers and Soldiers in the Election to the Constitutive Seim of Lithuania in 1920 - Kilinskas, Kęstutis (Lietuvos istorijos studijos, 2018)
The author analyzes the voting rights issue of officers and soldiers regarding the Constitutive Seim of Lithuania. The positions of the main Lithuanian national election commission and the main political parties, consisting of the Christian Democrats, Social Democrats, Socialist Democrats and the Santara parties are introduced and explained in the article. A lot of attention is focused on finding out an accurate number of officers and soldiers who participated in the election of the Constitutive Seim as candidates of politicals. The author also seeks to emphasize colleration between the opinions of political parties and the number of soldiers in the election list of a particular political party. The biggest part of Lithuanian officers and soldiers who participated as candidates to the Constitutive Seim of Lithuania had done so as members of left-wing political parties, because they shared positive attitudes toward and supported the idea of an active vote right for officers and soldiers. There were also three different atittudes about voting rights in the military forces; some unit commanders where opposed to it due to agitation, officer candidates of left-wing parties supported the idea of an active vote right, and the same opinion was also expressed by the official army magazine.
Keywords: Constitutive Seim; armed forces; soldiers and officers vote right; agitation; political parties; law of election